2020
DOI: 10.3390/electronics9010181
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intrusion Detection Model Using a Fusion of Network and Device States for Communication-Based Train Control Systems

Abstract: Security is crucial in cyber-physical systems (CPS). As a typical CPS, the communication-based train control (CBTC) system is facing increasingly serious cyber-attacks. Intrusion detection systems (IDSs) are vital to protect the system against cyber-attacks. The traditional IDS cannot distinguish between cyber-attacks and system faults. Furthermore, the design of the traditional IDS does not take the principles of CBTC systems into consideration. When deployed, it cannot effectively detect cyber-attacks agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Machine learning methods for intrusion detection no longer rely on rule matching but instead build classification models to distinguish between normal and malicious traffic [9]. Support vector machines (SVMs) have been widely used for intrusion detection, and by combining SVM with feature selection techniques, the feasibility and effectiveness of intrusion detection can be enhanced [10].…”
Section: Background 21 Intrusion Detectionmentioning
confidence: 99%
“…Machine learning methods for intrusion detection no longer rely on rule matching but instead build classification models to distinguish between normal and malicious traffic [9]. Support vector machines (SVMs) have been widely used for intrusion detection, and by combining SVM with feature selection techniques, the feasibility and effectiveness of intrusion detection can be enhanced [10].…”
Section: Background 21 Intrusion Detectionmentioning
confidence: 99%
“…However, implementing a traditional anomaly-based intrusion detection system (IDS) is not enough, because the traditional IDS may produce a false positive alarm caused by a system fault. A further study was reported in [ 17 ], which proposed an intrusion detection model using a fusion of network and device states. The proposed method can identify the difference between the abnormality among anomalies caused by cyber-attacks and by system faults.…”
Section: Related Workmentioning
confidence: 99%
“…Other than the anomaly-based model, various types of intrusion detection techniques are also used in the defense mechanism. Different machine learning and deep learningbased algorithms are showing high detection accuracy [18]- [21]. For classification type IDS, supervised learning is widely used, and unsupervised learning is usually used for clustering based IDS [22].…”
Section: B Intrusion Detection Systems In Cpsmentioning
confidence: 99%